De-Escalation Training Receptivity and First-Line Police Supervision: Findings from the Louisville Metro Police Study. (June 2022) - Engel, Robin S.; Isaza, Gabrielle T.; Motz, Ryan T.; McManus, Hannah D.; Corsaro, Nicholas
Despite calls for police reform that include changes to use of force training and field supervision, evidence regarding their impact is sorely lacking. This study examines survey data collected from first-line supervisors in the Louisville (KY) Metro Police Department after department-wide de-escalation training. Presented as part of a larger randomized controlled trial study, descriptive results from this survey demonstrate that, despite high levels of reported confidence in supervisory ability, supervisors infrequently engage in the activities that support and reinforce subordinates' use of de-escalation skills. Results from multivariate ordinary least squares (OLS) linear regression models further show that only supervisors' receptivity to de-escalation training is a significant predictor of engaging in activities that support the training tenets for subordinates. Combined with previous findings, the emerging research and policy implications suggest that training receptivity is critical, and further, that field supervision continues to be an under-utilized mechanism to reduce police use of force.